CONCEPTIONS OF LITERARY CRITICISM OF YURIY BOIKO-BLOKHYN IN THE INVESTIGATION ABOUT TARAS SHEVCHENKO’S WORKS - Khorob S. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article has the investigation of the conceptions of literary criticism of the Ukrainian scientist from diaspora Yuriy Boiko-Blokhyn in his scientific works about the life and creation of Taras Shevchenko. The author made an effort to systematize them, extrapolating his outlook in present-day time.